2021
DOI: 10.1155/2021/4532438
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Biomarkers for Predicting Prognosis and Immunotherapy Response in Head and Neck Squamous Cell Carcinoma Based on ceRNA Network and Immune Infiltration Analysis

Abstract: Objectives. Patients with head and neck squamous cell carcinoma (HNSCC) have poor prognosis and show poor responses to immune checkpoint (IC) inhibitor (ICI) therapy. Competing endogenous RNA (ceRNA) networks, tumor-infiltrating immune cells (TIICs), and ICIs may influence tumor prognosis and response rates to ICI therapy. This study is aimed at identifying prognostic and IC-related biomarkers and key TIIC signatures to improve prognosis and ICI therapy response in HNSCC patients. Methods and Results. Ninety-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…IL1B can also enhance the signal transduction of CTLA4, and targeting the IL1B-CTLA4 axis can effectively inhibit the occurrence of metastatic and recurrent colon cancer (69). ITGA5 is a crucial immunotherapy predictive target that is thought to be crucial in the incidence and progression of many cancers (70)(71)(72). CST7 is associated with activation of CD4T and CD8T cells in liver cancer (73).…”
Section: Discussionmentioning
confidence: 99%
“…IL1B can also enhance the signal transduction of CTLA4, and targeting the IL1B-CTLA4 axis can effectively inhibit the occurrence of metastatic and recurrent colon cancer (69). ITGA5 is a crucial immunotherapy predictive target that is thought to be crucial in the incidence and progression of many cancers (70)(71)(72). CST7 is associated with activation of CD4T and CD8T cells in liver cancer (73).…”
Section: Discussionmentioning
confidence: 99%
“…TMC7 was identi ed as a potential prognostic biomarker for pancreatic cancer, and its high expression was associated with a poor prognosis (33). An early study said TMC7 expression negatively correlated with CTLA4, HAVCR2, LAG3, PDCD1, and TIGIT expression in head and neck squamous cell carcinoma (45). In contrast, our research came to the opposite conclusion in RCCC.…”
Section: Discussionmentioning
confidence: 46%
“…Different types of cancer have different proportions of infiltrating immune cells, which affects immunological response and prognosis 7 . Recent research has shown that ceRNA networks participate in tumor cell-immune system communication, and several molecular signatures are biomarkers for this crosstalk 8,9 www.nature.com/scientificreports/ the coinhibitory receptor programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1), which have revolutionized cancer therapy for the past few years. The TME also affects the degree of the immune checkpoint inhibition response in HNSCC 10 .…”
Section: Identification Of a Novel Cerna Network Related To Prognosis...mentioning
confidence: 99%
“…Earlier research into ceRNAs in HNSCC found many RNAs linked to patients OS [30][31][32] . Guo et al constructed two risk signatures on nine ceRNAs (ANLN, CFL2, ITGA5, KDELC1, KIF23, NFIA, PTX3, RELT, and TMC7) and three immune cell types (naïve B cells, neutrophils, and regulatory T cells) 9 . These immune cells also showed a correlation with our ceRNAs.…”
Section: High Plau Expression May Be Related To the Tumor Immune Resp...mentioning
confidence: 99%